Isotopic discrimination of natural and anthropogenic perchlorate sources in groundwater in a semi-arid region of northeastern Oregon (USA). (April 2022) - Hatzinger, Paul B.; Böhlke, J.K.; Jackson, W. Andrew; Gu, Baohua; Mroczkowski, Stanley J.; Sturchio, Neil C.
Abstract: Perchlorate (ClO4 − ) has synthetic and natural sources. Synthetic ClO4 − is released to the environment from its use as an oxidant in military and aerospace applications, and from its presence in a variety of common commercial products, such as safety flares, chlorate herbicides, and fireworks. Natural sources of ClO4 − in the environment include imported nitrate fertilizers derived from salt deposits in the Atacama Desert of Chile and indigenous natural ClO4 − that accumulates in unsaturated soils and groundwaters in other arid and semi-arid environments, largely from atmospheric deposition. The stable isotope ratios of chlorine ( 37 Cl/ 35 Cl) and oxygen ( 18 O/ 16 O, 17 O/ 16 O) and the isotopic abundance of radioactive 36 Cl in ClO4 − can be used to discriminate these different sources. Perchlorate was previously detected at relatively high concentrations (3.8–34.7 μg/L) in groundwater from many wells in the Boardman-Umatilla area near the Columbia River in northeastern Oregon, which is a semi-arid, highly agricultural, heavily irrigated area that includes several past and current military installations. Eight representative groundwater wells were sampled throughout this region and isotopic characteristics of ClO4 − collected from each well were measured along with other chemical and isotopic parameters including tritium and other groundwater age indicators. Isotopic data indicate that indigenous natural ClO4 − was present in groundwater from all sampled wells and was the predominant source in five of the wells. Synthetic ClO4 − was present in the three remaining wells with natural ClO4 −, and a minor fraction of Atacama-fertilizer-derived ClO4 − was indicated in one of the wells. Data from this study expand the geographic area of the USA in which indigenous natural ClO4 − has been detected to include the semi-arid northwest. This study also illustrates the role of irrigation recharge as a mechanism for producing relatively high concentrations of indigenous natural ClO4 − in groundwater by flushing accumulated salts from the unsaturated zone. Highlights: ClO4 − from three different sources was identified isotopically in groundwater. Indigenous natural ClO4 − appears to be the predominant source in groundwater. ClO4 − was flushed from unsaturated zone salt accumulations into groundwater by irrigation recharge.